Improving gelatin extraction from hide using plant enzyme - assisted process - Ahmad, Tanbir (2018)
Gelatin is a high molecular weight biopolymer obtained by partial denaturation of collagen brought by hydrolysis. Collagen being a structural protein having three α-chains intertwined by hydrogen and covalent bonds form a very stable right-handed triple helix which requires pretreatment by acid or alkali to convert it into gelatin. This results in low production of gelatin. In the past, researchers have used various proteases to improve the gelatin yield and quality. Use of protease enzymes led to increase in gelatin yield but simultaneous reduction of gelatin quality mainly due to production of gelatin having short chain polypeptides. Gelatin with high molecular weight polypeptides (less degraded peptides) are reported to be better in functional properties. Therefore, it was proposed to use novel enzymes which could cut the collagen chains in such a way so that longer chain proteins could be obtained in the resulting gelatin. Additionally, scanty research works are available on use of ultrasound to extract gelatin and its effect on the yield and quality. Therefore, ultrasound assisted gelatin extraction in conjugation with enzymes was taken up as an objective. Endopeptidase enzymes present in the skin are also reported to be activated at high extraction temperature and cause the degradation of the gelatin protein. Therefore, autolysis study was carried out and suitable endopeptidase inhibitor was used to extract the gelatin. Four plant enzymes namely actinidin (A), papain (P), bromelain (B) and zingibain (Z) were used to extract gelatin from bovine skin. The skins were pretreated for 48 h with these enzymes at the levels of 0, 5, 10, 15, 20 and 25 unit/g of skin at the respective optimum temperature and pH of the enzymes and the gelatin was extracted at 60 °C for 6 h. Significantly (P<0.05) higher gelatin of 22.67% was obtained from actinidin at the level of 20 unit/g (A20) than all other treatment levels of actinidin and control (17.90%). The yield from papain at level 20 (P20) was 23.59% yield. Gelatin extracted using actinidin enzyme (GEA) showed significantly (P<0.05) higher gel strength than the control (283.35) and other treatment group samples. Bromelain at level 15 (B15) and 25 (B25) gave gelatin yield of 23.25 and 23.49%, respectively which was highest than all other samples of gelatin extracted using bromelain (GEB) whereas zingibain at level 15 (Z15) gave the highest yield of 23.52% within the gelatin extracted using zingibain (GEZ) group. For A20, the gel strength was 366.39 g and least recorded gel strength in GEA samples was for A25 (348.56). Relatively low gel strength was recorded for the gelatin extracted using papain (GEP) as P10 exhibited the highest gel strength of 119.32 g within GEP treatment group. The yield and gel strength for B20 was 22.26% and 160.88 g, respectively and the least recorded gel strength was 111.56 g for B15 within the GEB group while the gelatin extracted using zingibain (GEZ) samples failed to form gel. Viscosities were significantly (P<0.05) higher for GEA samples compared to control gelatin (12.10 mPa.s) and all the treatment groups. Contrary to it, gelatin extracted using papain (GEP) showed lower viscosity than control. Viscosity of 13.53 mPa.s was noticed for A20 whereas within the GEP group, P25 exhibited the highest viscosity of 10.70 mPa.s. Viscosities of GEB were significantly (P<0.05) higher than GEZ samples. Among the treatment groups, lowest viscosities of 9.13 and 5.80 mPa.s were recorded in samples B15 and Z15, respectively. All the treatment samples and control showed complete degradation of β chains. GEA samples showed the presence of α chains and lower molecular weight peptides. GEP samples revealed complete degradation of β band along with α chains and lower molecular weight peptides were noticed in all GEP samples. All GEB and GEZ samples showed complete degradation of β and α chains. Low molecular weight peptides were observed in GEB samples. In contrast, GEZ samples revealed only smear bands with complete absence of protein band. Actinidin and bromelain enzymes were used to pretreat the bovine skin for 48 h and ultrasonic wave (53 kHz and 500 W) was used for the time durations of 2, 4 and 6 h at 60 °C to extract gelatin samples (UA2, UA4 and UA6, respectively for actinidin pretreated gelatins and UB2, UB4 and UB6, respectively for bromelain pretreated gelatins). Control (actinidin and bromelain pretreated, UAC and UAB, respectively) gelatin was extracted using ultrasound for 6 h at 60 °C without enzyme pretreatment. Ultrasound treatment led to significant increase in the gelatin yield as the time duration of ultrasonic treatment increased. UA6 gave significantly higher yield (19.65%) than UAC (18.72%) and UB6 yield (19.71%) was significantly higher compared to UBC (18.67%). The gel strength of UA6, UAC, UB6 and UBC were 502.16, 627.53, 595.51 and 603.24 (g), respectively. The corresponding viscosity was 15.60, 16.33, 16.37 and 16.33 mPa.s, respectively. Amino acid content was found to increase with the duration of ultrasound treatment and UAC and UBC showed the highest amino acid content in their respective treatment groups. Protein pattern of the extracted gelatin revealed progressive degradation with the time duration of ultrasound treatment. In ultrasound-actinidin gelatins, fourier transform infrared (FTIR) spectroscopy revealed loss of molecular order and degradation in UA6. Amide I band of gelatins extracted by ultrasound-bromelain treatment suggested greater loss of molecular order in these samples than the commercial gelatin (CG). Longer duration of ultrasound treatment caused inter-connected network formation, protein aggregation and small particle size as revealed by scanning electron microscopy (SEM). Although decreased structural integrity of the gelatin samples were observed with increase in ultrasound extraction time, UBC did not lose its structural integrity. Autolysis study of pretreated bovine skin (PS) showed that the maximal autolysis took place at 40 °C and pH 5. Various protease inhibitors were used to inhibit this autolysis and ethylene-bis (oxyethylenenitrilo) tetraacetic acid (EGTA) (10 mM) was found to inhibit the autolysis most effectively. EGTA being the preferentially calcium binder indicated that the metallocollagenases were the predominant endopeptidases present in the bovine skin. Subsequent to this, gelatin was extracted in the absence (GAI) and presence (GPI) of EGTA to study its effect on the extracted gelatin. PS was incubated at 10 °C for 24 h with 10 mM EGTA solution. Apart from this, one more gelatin sample was extracted using papain enzyme (GPIP). PS was treated with EGTA and then incubated with papain at 40 °C for 48 h. Gelatins were extracted in water bath at 60 °C for 6 h. The use of papain resulted in significantly (P<0.05) higher gelatin yield for GPIP (23.68%) than GAI (16.11%) and GPI (15.52%). Use of EGTA in GPI might led to non-significant (P>0.01) decrease in yield in GPI compared to GAI. GAI, GPI and GPIP exhibited gel strength of 554.90, 538.77 and 418.62 g, respectively. Molecular weight distribution showed complete degradation of β chains in all the samples and distinct inhibition of α chains in GPI was observed due to inhibitory effect of EGTA on endopeptidases. High intensities of α1 and α2 chains were noticed in GAI whereas there was complete degradation of α chains in GPIP gelatin. Molecular order was retained in GPI due to presence of EGTA and random coiled structure of GAI and GPIP was indicated as revealed by FTIR spectra. Finally, it can be concluded that actinidin and bromelain enzymes, particularly at level 20 unit/g of skin, could be used to enhance the extraction yield and quality characteristics of gelatin from bovine skin. Among these two enzymes, actinidin was better in improving the yield and quality characteristics of gelatin from bovine skin. Ultrasound assisted extraction in conjugation with actinidin and bromelain enzymes resulted in higher gelatin yield and quality. The gelatin yield of bovine skin gelatin, its quality, molecular weight distribution and secondary structures were influenced by metallocollagenases. Papain enzyme pretreatment of bovine skin subsequent to EGTA incubation improved gelatin yield but reduced gel strength.